A Process Mineralogy Approach to the Flotation of Complex Lead-Zinc Ores from Gorgu (Malatya) Region - Altinisik, Ceylan Yarlugkal; Cebeci, Yakup; Sis, Hikmet; Kalender, Leyla (Springer Heidelberg, 2022)
Complex and non-sulfide lead-zinc ores are difficult to concentrate, but the growing demand for lead and zinc metals necessitated their beneficiation. Froth flotation is practically the most effective method in their beneficiation when optimum flotation conditions are attained. The aim of the current study is to use process mineralogy as a tool to understand the flotation behavior of these complex lead-zinc ores. The ore samples were characterized by element, XRD, MLA, thin section, and polished section mineralogical analysis, which clearly demonstrated oxidation and carbonation of the primary minerals. In the rougher flotation stage, a lead concentrate with 17.29% Pb and a zinc concentrate with 9.89% Zn could be obtained by 76.71% lead and 15.49% zinc recoveries from the ore samples containing 7.84% Zn and 4.54% Pb. The flotation results were delineated by process mineralogy data and poor results were explained in terms of (i) complex nature of the ore and similarity in the surfaces of different mineral particles, (ii) poly-metallic occurrence and spatial distribution of elements, (iii) poor liberation of particles, and (iv) lack of hydrophobicity on particle surfaces.
Keywords: Process mineralogy; Froth flotation; Pb-Zn ores; Oxidation; alteration; Mineral liberation analysis